2019
DOI: 10.6007/ijarbss/v9-i14/6499
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Triaging For Patients in the Emergency Department: Overview, Aims, Guideline, and Challenges

Abstract: Congestion in emergency departments is an overall issue. Triaging includes an underlying arranging of patients who arrive at the Emergency Department (ED), keeping in mind the end goal is to organize the most emergency patients and to guarantee giving them the proper and quick healthcare needed. This study plans to survey the models, guidelines, advancement of the electronic triage procedures of the triaging frameworks. Likewise, the goals of this investigation are to experimentally investigate and show the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Besides, another study indicated that the NIH syndrome was one of the obstacles for collaboration [71][72]. When an enterprise had a strong internal technical team, it could suffer the same syndrome, and not be accepted external ideas or not completely collaborate with external service providers [43,72]. On the other hand, this findings is in contrast with other researchers such as Han, Lee [27], since they found that the firm's IT capability positively effects the information sharing level, the degree of communication quality and collaborative participation.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, another study indicated that the NIH syndrome was one of the obstacles for collaboration [71][72]. When an enterprise had a strong internal technical team, it could suffer the same syndrome, and not be accepted external ideas or not completely collaborate with external service providers [43,72]. On the other hand, this findings is in contrast with other researchers such as Han, Lee [27], since they found that the firm's IT capability positively effects the information sharing level, the degree of communication quality and collaborative participation.…”
Section: Discussionmentioning
confidence: 99%